Association between edaravone use and activities of daily living in older patients with atherothrombotic stroke: an observational study using Japanese real-world data - Yukari Ogawa; Hiroko Akiyama; Takeshi Horii; Kiyoshi Mihara (BMC Geriatrics)
Abstract Background Edaravone is marketed in nine countries, although only Japan has approved edaravone for improvement of neurological symptom, disability of activities of daily living (ADL), and functional disability associated with acute stroke. This study aimed to elucidate the association of edaravone use with ADL using real-world data of older patients with atherothrombotic stroke. Methods This retrospective observational research using the Medical Data Vision database in Japan included patients aged 65 years and older who had acute ischemic stroke of the atherothrombotic subtype. Primary outcome was ADL improvement defined as change in Barthel Index from admission to discharge of greater than zero points. The major secondary outcome was good functional outcome (Barthel Index ≥ 90 or modified Rankin Scale 0–2 at discharge). Multivariate logistic regression analyses were conducted to calculate odds ratios with 95% confidence intervals for the outcomes. We further compared the change in Barthel Index from admission to discharge and in-hospital death rate between the edaravone- and non-edaravone- treated patients. Results A total of 5,576 patients were included in this study, and were divided into edaravone group (n = 3,825) and non-edaravone group (n = 1,751). The median age of this cohort was 79 years, and median Barthel Index at admission was 30 points. Edaravone use was associated with improved ADL with an adjusted odds ratio of 1.18 (95% confidence interval: 1.01‒1.37). However, no significant association was observed between edaravone use and good functional outcome. The edaravone group had significantly greater change in Barthel Index from admission to discharge than the non-edaravone group, with a difference of 5 points. The in-hospital death rate was comparable between the two groups. Conclusions Edaravone use may contribute to improve ADL at discharge in patients aged 65 years and older with atherothrombotic stroke.